Comparative study on Credit Performance of NABIL Bank Limited and Nepal Bank Limited - Kaphle, Deepak Prasad (Journal of Balkumari College, 2024)
This study researches into the relationship between credit performance and profitability in Nabil Bank and Nepal Bank Limited. Employing linear multiple regression analysis on ten years of financial data (2013/14 - 2022/23), the research explores how credit-related factors influence a key profitability metric - Return on Assets (ROA). The analysis in SPSS software facilitates a comparison between the two banks, highlighting how credit variables exert varying degrees of influence on their ROA. Interestingly, credit factors hold a stronger explanatory power for Nabil Bank’s profitability. Conversely, Loan Loss Provisions (LLPL) and Loan Loss Provision to Net Profit Loan (LLPNPL) emerge as significant negative influences on Nepal Bank’s profitability. These findings suggest potential differences in credit risk management between the two banks. Nabil Bank might exhibit stricter loan approval processes or more accurate loan loss provisioning compared to Nepal Bank Limited. Further research could investigate deeper into these specific credit management practices to provide a more comprehensive understanding of the factors driving the observed profitability variations.